Anti-Politics Machine: Development, Depoliticization, and Bureaucratic Power in Lesotho - Ferguson, James (University Of Minnesota Press, 1994)
Development, it is generally assumed, is good and necessary, and in it s name the West has intervened, implementing all manner of projects in the impoverished regions of the world. When these projects fail, as t hey do with astonishing regularity, they nonetheless produce a host of regular and unacknowledged effects, including the expansion of bureau cratic state power and the translation of the political realities of p overty and powerlessness into "technical" problems awaiting solution b y "development" agencies and experts. It is the political intelligibil ity of these effects, along with the process that produces them, that this book seeks to illuminate through a detailed case study of the wor kings of the "development" industry in one country, Lesotho, and in on e "development" project.Using an anthropological approach grounded in the work of Foucault, James Ferguson analyzes the institutional framew ork within which such projects are crafted and the nature of "developm ent discourse," revealing how it is that, despite all the "expertise" that goes into formulating development projects, they nonetheless ofte n demonstrate a startling ignorance of the historical and political re alities of the locale they are intended to help. In a close examinatio n of the attempted implementation of the Thaba-Tseka project in Lesoth o, Ferguson shows how such a misguided approach plays out, how, in fac t, the "development" apparatus in Lesotho acts as an "anti-politics ma chine," everywhere whisking political realities out of sight and all t he while performing, almost unnoticed, its own pre-eminently political operation of strengthening the state presence in the local region.Jam es Ferguson is an associate professor of anthropology at the Universit y of California at Irvine.